Problems in the Tibetan Region: China and Its Efforts to Suppress Self-Determination by the Tibetan Society - Ranti, Munif Arif; Juliana, Cindy; Izzatinnisa (Hasanuddin Journal of International Affairs, 2025)
As a minority, Tibetans struggle to realize self-determination amidst the onslaught of oppression by China so that they can achieve freedom. Using a constructivist approach, this research analyzes China's dynamics in suppressing the fulfillment of Tibetan self-determination. The suppression carried out by China represents its more assertive position in the problems in Tibet, as well as being an idea that shows the interest in aligning Chinese identity, which makes the problems of minority groups a threat of separatism. The findings of this research include several main notes. China has succeeded in suppressing Tibet's position through various actions ranging from strengthening constructions related to Tibetan history and identity that can benefit its internal position, emphasizing securitization in the Tibetan issue to expand its sovereignty in peripheral areas, practicing modern colonialism, and strengthening the practice of particularism and creating a "New Era of China" that can limit Tibetan society. Thus, the self-determination that the Tibetan people want to achieve will only be an unrealizable wishful thinking.